2005
DOI: 10.1189/jlb.0205120
|View full text |Cite
|
Sign up to set email alerts
|

Professional phagocytic granulocytes of the bony fish gilthead seabream display functional adaptation to testicular microenvironment

Abstract: It has been shown previously that professional phagocytic granulocytes are present in the testis of the gilthead seabream, a seasonal breeding teleost that offers an excellent model for studying the testicular regression process that occurs in seasonal testicular involution and sex change. It is unexpected that testicular granulocytes produce interleukin-1␤, a regulator for spermatogonia proliferation in mammals, but are not involved in the elimination of degenerative germ cells. Here, we show that phagocytosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 26 publications
2
56
0
Order By: Relevance
“…The G7 also allowed applying the MACS techniques using micromagnetic-beads to specific purified acidophilic granulocytes guaranteeing the viability and functional characteristics of these cells as occurred in mammals (Miltenyi et al, 1990) (Figure 7). Thus, we demonstrated that the main functional activities of acidophilic granulocytes are inhibited once they migrated into the testis (Chaves-Pozo et al, 2005b). As previously discussed (see point 4) each antibody allowed a fixed number of techniques that depended on its ability to react with its specific epitope under native or denatured conditions.…”
Section: Flow Cytometry and Magnetic Activating Cell Sorting (Macs)mentioning
confidence: 63%
See 4 more Smart Citations
“…The G7 also allowed applying the MACS techniques using micromagnetic-beads to specific purified acidophilic granulocytes guaranteeing the viability and functional characteristics of these cells as occurred in mammals (Miltenyi et al, 1990) (Figure 7). Thus, we demonstrated that the main functional activities of acidophilic granulocytes are inhibited once they migrated into the testis (Chaves-Pozo et al, 2005b). As previously discussed (see point 4) each antibody allowed a fixed number of techniques that depended on its ability to react with its specific epitope under native or denatured conditions.…”
Section: Flow Cytometry and Magnetic Activating Cell Sorting (Macs)mentioning
confidence: 63%
“…In that sense we have first performed the phagocytic assay (review in Esteban et al, 1998), and then the immunostaining keeping the cells at 4ºC to avoid digestion of the phagocyted-fluorescence-bacteria and internalization of the antigen-antibody complex at the membrane. Thus, we have observed that the 95% of the head-kidney acidophilic granulocytes had phagocytic capability in contrast with the 1% of the testicular acidophilic granulocytes (Chaves-Pozo et al, 2005b;Sepulcre et al, 2002). However, most of the functional activities of the immune response can not be combine with a posterior antibody immunostaining, so the purification of the testicular acidophilic granulocytes were mandatory to really understand the role of the acidophilic granulocytes once they migrated into the gonad.…”
Section: Flow Cytometry and Magnetic Activating Cell Sorting (Macs)mentioning
confidence: 99%
See 3 more Smart Citations